2017
DOI: 10.1002/ajp.22726
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of samples from wild populations opens new perspectives on hybridization between long‐tailed (Macaca fascicularis) and rhesus macaques (Macaca mulatta)

Abstract: In the past decade, many researchers have published papers about hybridization between long-tailed and rhesus macaques. These previous works have proposed unidirectional gene flow with the Isthmus of Kra as the zoogeographical barrier of hybridization. However, these reports analyzed specimens of unknown origin and/or did not include specimens from Thailand, the center of the proposed area of hybridization. Collected specimens of long-tailed and rhesus macaques representing all suspected hybridization areas we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(86 citation statements)
references
References 37 publications
7
75
0
Order By: Relevance
“…Using Premasuthan et al's methods, Kanthaswamy et al reported the presence of indeterminate blood types in cynomolgus and rhesus macaque populations at frequencies of 2.39% and 1.18%, respectively, and Oldt et al described an enrichment of indeterminate blood phenotypes in the hybrid zone shared by the two species as speculated previously . Multiple macaques in Oldt et al's study exhibited an indeterminate allele caused by failure of the first probe to bind with its target site coupled with the successful detection of the A or B allele with the second probe, suggesting that the indeterminate phenotypes are generated by probe‐target hybridization failures which point to an underlying genetic cause rather than DNA degradation …”
Section: Introductionmentioning
confidence: 83%
“…Using Premasuthan et al's methods, Kanthaswamy et al reported the presence of indeterminate blood types in cynomolgus and rhesus macaque populations at frequencies of 2.39% and 1.18%, respectively, and Oldt et al described an enrichment of indeterminate blood phenotypes in the hybrid zone shared by the two species as speculated previously . Multiple macaques in Oldt et al's study exhibited an indeterminate allele caused by failure of the first probe to bind with its target site coupled with the successful detection of the A or B allele with the second probe, suggesting that the indeterminate phenotypes are generated by probe‐target hybridization failures which point to an underlying genetic cause rather than DNA degradation …”
Section: Introductionmentioning
confidence: 83%
“…DNA samples from 222 free‐ranging macaques, comprising 8 rhesus and cynomolgus populations living in the hybrid zone described in Bunlungsup, Kanthaswamy, et al () as well as 30 wild‐caught cynomolgus macaques from Laos, were subjected to molecular phenotyping using the dual‐amplification qPCR procedure developed by Premasuthan et al (), and blood group frequencies were calculated assuming absence of an O allele. The nine populations studied consist of four rhesus macaque populations from Myanmar, Thailand, and Laos and five cynomolgus macaque populations from Laos and Thailand (both North and South of the IoK; Bunlungsup, Kanthaswamy, et al, ). Blood group frequency reference data (Kanthaswamy et al, ) consisted of two rhesus macaque populations of Chinese and Indian ancestry, three cynomolgus macaque populations of Indonesian, Philippine and Mauritian ancestry, and one population of Vietnam/Cambodia cynomolgus macaque which was treated as the tenth hybrid population.…”
Section: Methodsmentioning
confidence: 99%
“…The locations of Chinese and Indian rhesus reference populations, hybrid populations of rhesus and cynomolgus macaques, and cynomolgus reference populations were shown in Tables –, and Figure . To compare distributions between the two species, the species status as determined in Bunlungsup, Kanthaswamy, et al () was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bunlungsup et al 2017;Liu et al 2018). Therefore, a more detailed and comprehensive evolutionary history of macaques should be performed using species-wide genome sequences in future studies.…”
mentioning
confidence: 99%